Towards a Comprehensive Metaverse Forensic Framework Based on Technology Task Fit Model - Amna AlMutawa; Richard Adeyemi Ikuesan; Huwida Said (Future Internet)
This article introduces a robust metaverse forensic framework designed to facilitate the investigation of cybercrime within the dynamic and complex digital metaverse. In response to the growing potential for nefarious activities in this technological landscape, the framework is meticulously developed and aligned with international standardization, ensuring a comprehensive, reliable, and flexible approach to forensic investigations. Comprising seven distinct phases, including a crucial incident pre-response phase, the framework offers a detailed step-by-step guide that can be readily applied to any virtualized platform. Unlike previous studies that have primarily adapted the existing digital forensic methodologies, this proposed framework fills a critical research gap by providing a proactive and granular investigative process. The approach goes beyond mere adaptation, ensuring a comprehensive strategy that addresses the unique challenges posed by the metaverse environment. The seven phases cover a spectrum of forensic investigation, offering a thorough interpretation with careful consideration of real-life metaverse forensic scenarios. To validate its effectiveness, the proposed framework undergoes a rigorous evaluation against the appropriate ISO/IEC standards. Additionally, metaverse expert reviews, based on the task–technology fit theory, contribute valuable insights. The overall assessment confirms the framework’s adherence to forensic standards, making it a reliable guide for investigators navigating the complexities of cybercrime in the metaverse. This comprehensive metaverse forensic framework provides investigators with a detailed and adaptable tool to address a wide range of cybercrime incidents within the evolving virtualized landscape. Furthermore, its stepwise guidance ensures a thorough and reliable investigation process, offering significant contributions to proactive security measures in the face of emerging challenges in the metaverse.